CATAZONE TECTONO-FACIES FROM AREA OF TECTONIC FLOW IN GRANITE - LUKIIENKO, O.; KRAVCHENKO, D.; SUKHORADA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The granite tectono-facies of catazone examine as dislocation facias, which represent comparative intensity of rock deformation take into account pressure-temperature conditions and mechanism of transformations. Indications of tectono-facies were brought according to ten-point scale.